2008
DOI: 10.1111/j.1468-2958.2008.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Tower, Am I Cleared to Land?: Problematic Communication in Aviation Discourse

Abstract: This study examined problematic communication in pilot-air traffic controller (ATC) interaction. More than 15 hours of pilot-ATC dialogue were collected by monitoring control tower frequencies at 15 U.S. airports. The transcribed data yielded a total of 34 ATCs, 270 pilots, and 1,799 turns of talk. Analyses revealed that (a) communication problematics manifested in pilot turns more than ATC turns, (b) higher amounts of information led to increased problematic communication in the subsequent turn, and (c) lingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 30 publications
3
26
0
2
Order By: Relevance
“…Interestingly, all turns in plain English by this pilot were ultimately replaced with phraseology which suggests that overuse of plain English is not entirely due to the limitations of the existing phraseology repertoire, but at least partly to a view that this is what is needed in abnormal or emergency situations. This finding accords with those of studies conducted in the US radiotelephony context (Morrow et al 1994;Howard, 2008), where interlocutors are for the most part native speakers of English. These scholars report that when the communication becomes problematic, plain English tends to be favoured by speakers and addressees to make sure that what they have understood and/or are understood correctly.…”
Section: Discussion and Recommendationssupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, all turns in plain English by this pilot were ultimately replaced with phraseology which suggests that overuse of plain English is not entirely due to the limitations of the existing phraseology repertoire, but at least partly to a view that this is what is needed in abnormal or emergency situations. This finding accords with those of studies conducted in the US radiotelephony context (Morrow et al 1994;Howard, 2008), where interlocutors are for the most part native speakers of English. These scholars report that when the communication becomes problematic, plain English tends to be favoured by speakers and addressees to make sure that what they have understood and/or are understood correctly.…”
Section: Discussion and Recommendationssupporting
confidence: 90%
“…In the literature on radiotelephony communication in the US setting, it has been shown that when radiotelephony communication deviates from routine phraseology use, plain English is favoured by speakers and addressees in order to make sure that they have understood correctly and have been understood by their interlocutor (Morrow et al, 1994;Howard, 2008). However, these scholars also found, through analysis of an extended corpus of radiotelephony communication, that when a turn contains many units of information or when deviation from phraseology occurs, the communication may become problematic.…”
Section: Plain Language (English)mentioning
confidence: 99%
“…He found that communication issues or related problems occurred more often in the pilot side than the ATC side of the communication, and increasing the amount of information included in a particular transmission led to problems in the next communication. Howard (2008) also determined that changes to ATC protocol in transmitting information to aircrews led to problems in follow-on communication.…”
mentioning
confidence: 99%
“…Howard (2008) investigated pilot-ATC communication, observing control tower frequencies at 15 U.S. airports. He found that communication issues or related problems occurred more often in the pilot side than the ATC side of the communication, and increasing the amount of information included in a particular transmission led to problems in the next communication.…”
mentioning
confidence: 99%
“…Douglas (2004) highlights that it is necessary to identify the nature of aviation English, both the standardized phraseology and plain English, the relationship between them, and the situations when each is adopted. Research (Howard, 2008;Kim & Elder, 2009) has shown that plain English tends to be adopted when speakers are involved in abnormal or emergency circumstances, even when aviation phraseology could suffice. Such underutilization of aviation phraseology results in more complex use of structure and vocabulary and could prompt a communication problem between speakers.…”
Section: Definition Of Aviation Englishmentioning
confidence: 99%